Intracellular Distribution and Biological Effects of Phytochemicals in a Sex Steroid- Sensitive Model of Human Prostate Adenocarcinoma - Smeriglio, Antonella; Trombetta, Domenico; Marcoccia, Daniele; Narciso, Laura; Mantovani, Alberto; Lorenzetti, Stefano (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Prostate function is critical for male fertility and its well-known oncological biomarker, namely Prostate-Specific Antigen (PSA), can be also used to monitor prostate epithelial human cells upon treatment with pharmaceutical drugs or natural bioactive compounds. The LNCaP human prostate cell line was previously set up as a model system to investigate chemicals affecting prostate epithelium functionality by means of a tiered approach integrating two different toxicological endpoints, cell viability (MTS) and PSA secretion assays. Here, the same approach has been used to characterize the biological effects of phytochemicals on prostate epithelium. The antiandrogenic ability of phytochemicals to inhibit DHT-induced PSA secretion has been investigated also characterizing their intracellular distribution, in the presence or absence of sex steroids. Intracellular distribution allows to verify whether and to which extent each phytochemical is able to enter the cell and to reach the nucleus, the latter being the target of the supposed transcriptional modulatory activity upon phytochemicals’ binding to sex steroid receptors. Some phytochemicals, supposed to have a role in the functionality of the prostate epithelium, have been tested in a dose-dependent manner in both MTS and PSA secretion assays. In parallel, to establish the “effective concentration”, in comparison to the “nominal one”, the intracellular amount of each phytochemical has been assessed upon cell fractionation of LNCaP-treated cells and subsequent chromatographic measurements.
Keywords: cytotoxicity